2020
DOI: 10.3389/fimmu.2020.00919
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of de novo Donor-Specific Antibody Subclasses Quantified by Mass Spectrometry: High IgG3 Proportion Is Associated With Antibody-Mediated Rejection Occurrence and Severity

Abstract: Donor-specific antibodies (DSAs) are the main risk factor for antibody-mediated rejection (ABMR) and graft loss but could have variable pathogenicity according to their IgG subclass composition. Luminex-based test might lack sensitivity for the detection of IgG subclasses and this test does not allow quantifying the relative abundance of each IgG subclass. We investigated the precise repartition of each DSA subclass and their role in ABMR occurrence and severity, using an innovative mass spectrometry-based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…7,8,30 Using a more sensitive mass spectrometry-based method, the four IgG subclasses were detected for all DSA and a higher proportion of IgG3 subclass was associated with the occurrence and severity of ABMR, confirming our recently results reported. 32 These data suggest that the IgG3 subclass is particularly involved in the physiopathology of ABMR.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…7,8,30 Using a more sensitive mass spectrometry-based method, the four IgG subclasses were detected for all DSA and a higher proportion of IgG3 subclass was associated with the occurrence and severity of ABMR, confirming our recently results reported. 32 These data suggest that the IgG3 subclass is particularly involved in the physiopathology of ABMR.…”
Section: Discussionmentioning
confidence: 89%
“…Relative quantification of the IgG subclasses was performed as previously described. 32 Peptides and proteins were identified using the ProteinPilot software v.5.0 (Sciex). Each IgG subclass was quantified using two unique proteotypic peptide sequences (Table S1).…”
Section: Methods For Dndsa Igg Subclass Quantification By Mass Spectr...mentioning
confidence: 99%
See 1 more Smart Citation
“…40 In contrary to our findings, Pernin et al, 2020, assessed DSAs IgG subclasses in 69 KT recipients by using mass spectrometry after DSA isolation and that allowing their relative quantification. 15 They reported that all IgG subclasses were present in post-TX de novo DSA as IgG1 was predominant (62.2% of total IgG), IgG2 (23.1%), IgG3 (7.8%) and IgG4 (4.7%). Thus, IgG1, IgG3 and IgG4 fractions were high in alloimmune response than in total IgG and AMR occurrence with poor graft outcome, correlated with high IgG3 DSA percentage.…”
Section: Discussionmentioning
confidence: 98%
“…Some of them reported that presence of IgG3 is associated with poor graft outcome. 14,15 In the past decades, the short-term graft survival in KT recipients was improved, with no noticeable improvement in long-term graft survival. 16,17 The present work aimed to analyze the distribution of anti-HLA class I and class II PRA, IgG, and its subclasses in the pre and post KT period and their association with acute AMR and graft survival.…”
Section: Introductionmentioning
confidence: 99%